Комплексне використання поновлюваних джерел енергії в умовах сільського подвір’я - Кузик, М.; Мисак, Й.; Івасик, Я. (Видавництво Національного університету “Львівська політехніка”, 2004)
The complex use of renewable sourses of energy in rural communities. The article explores possible setur for complex use of renewable sourses of energy in rural communities. The configuration includes biogasgenerator, solar collector, concentrator and pool. It’s shown that farm that uses disel generator and grows crops wits high biomass content 50 acres of land can be fully sustainable in satisfying its needs in thermal and electrical energy.
Keywords: 621; 311